High Kynurenine (a Tryptophan Metabolite) Predicts Remission in Patients with Major Depression to Add-on Treatment with Celecoxib - Krause, Daniela; Myint, Aye-Mu; Schuett, Christine; Musil, Richard; Dehning, Sandra; Cerovecki, Anja; Riedel, Michael; Arolt, Volker; Schwarz, Markus J.; Müller, Norbert (Frontiers in Psychiatry, 2017)
Background Signs of an inflammatory process have been described in major depression. Methods In a double-blind, randomized study of celecoxib or placebo add-on to reboxetine in 40 depressed patients, celecoxib treatment has beneficial effects. In order to evaluate the tryptophan/kynurenine metabolism and to identify predictors for remission, tryptophan (TRP), kynurenine (KYN), kynurenic acid (KYNA), and quinolinic acid (QUIN) were estimated in the serum of 32 patients before and after treatment and in a group of 20 healthy controls. Results KYN levels were significantly lower in patients (p = 0.008), and the QUIN/KYN ratios were significantly higher (p = 0.028). At baseline, the higher KYN/TRP ratio was predictive for remission during celecoxib add-on treatment (p = 0.04) as well as for remission in the overall patient group (p = 0.01). In the placebo group, remitters showed a higher KYNA/QUIN ratio (p = 0.032). In the overall group, remitters showed lower KYNA/KYN (p = 0.035) and QUIN/KYN (p = 0.011) ratios. The lower the formation of downstream metabolites, especially QUIN, the better the treatment outcome. Conclusion The high KYN/TRP ratio predicted remission after treatment with celecoxib in this small sample of depressed patients. Eventually, the KYN/TRP ratio might be a marker for those patients, which benefit from an additional anti-inflammatory treatment.